A Versatile Ambient‐to‐High‐Pressure Reaction Transmission Cell for in situ/operando Infrared Spectroscopic Investigations. Issue 7 (1st July 2021) - Weiß, Jana; Rautenberg, Christine; Rall, Thomas; Kubis, Christoph; Kondratenko, Evgenii; Bentrup, Ursula; Brückner, Angelika
Abstract: Invited for this month's cover is the group of Angelika Brücker at the Leibniz Institute for Catalysis in Rostock (Germany). The cover picture shows a self‐developed stainless‐steel reaction cell for operando transmission FTIR studies of heterogeneous catalytic gas‐phase reactions at pressures up to 30 bar and temperatures up to 300°C, which is connected to a mass spectrometer for online product analysis. The performance of the cell has been tested in three types of CO2 hydrogenation reactions (CO2 Fischer‐Tropsch synthesis, CO2 methanation, CO2 conversion to dimethyl ether) on various solid catalysts implemented as self‐supporting wafers. Catalytic data obtained with this cell showed the same trends as those measured in a fixed‐bed plug‐flow reactor, thus confirming their reliability. Read the full text of their Full Paper at 10.1002/cmtd.202100024 . Abstract : "… The cell is small, compact, easy to handle, fits into different spectrometers and can be used for a wide variety of solid‐gas reactions… " Find out more about the story behind the front cover research at 10.1002/cmtd.202100024 .